Urgensi Swab Antigen Sebagai Syarat Perkawinan Persepektif Maqashid Al Syari'ah - Janeko, Janeko; Sholihuddin, Sholihuddin (JOSH: Journal of Sharia, 2022)
In 2019, the world was stirred by the outbreak of the COVID-19 virus, including in Indonesia, it had an impact on changes in the existing order, including marriage. Through Circular Number: P-001/DJ.III/HK.007/07/2021 Regarding Technical Instructions for Marriage Services at the Office of Religious Affairs During the Enforcement of Restrictions on Community Activities, with regard to the implementation of marriages, it is regulated in a different way than before the outbreak Corona virus, including the obligation of an antigen swab for the penghulu, prospective brides and witnesses 1x24 hours at the implementation of the marriage contract. This obligation is certainly a new and very interesting thing to do an in-depth study. This research includes normative legal research using qualitative methods, while the type of research includes literature research and is qualitative using descriptive analysis, the legal sources used include primary and secondary legal sources. The results of his research are the urgency of the antigen swab as a marriage requirement as a preventive measure. The antigen swab test is in accordance with the five main objectives of Islamic law, especially to protect the soul, so the antigen swab test is a process that must be carried out by the head of the bride and groom and witnesses in an effort to find out what is affected by the corona virus. In the category of protecting the soul, the pre-marital swab test process is included in the maqashid dharuriyyat category which is a primary need for humans because it will threaten the safety of life.